Identification of nanoparticle-mediated siRNA-ASPN as a key gene target in the treatment of keloids - Dong, Yipeng; Zhang, Chuwei; Zhang, Qingrong; Li, Zihan; Wang, Yixiao; Yan, Jun; Wu, Gujie; Qiu, Ling; Zhu, Zhihan; Wang, Bolin; Gu, Haiying; Zhang, Yi (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Keloid, also known as connective tissue hyperplasia, is a benign proliferative disorder with a global distribution. The available therapeutic interventions are steroid injections, surgical removal of keloids, radiotherapy, compression therapy, the application of cryosurgery, and many other methods. Objectives: Existing treatments or approaches for keloids may lead to similar or even larger lesions at the site of keloid excision, leading to a high recurrence rate. Therefore, this study aims at identifying a new gene-based therapy for the treatment of keloids. Methods: An ASPN-siRNA/nanoparticle combination (si-ASPN) and a negative siRNA/nanoparticle complex (NC) was developed on the basis of bioinformatics studies and used in vitro and in vivo experiments. Results: The results showed a strong correlation between the development of keloids and high expression of ASPN protein. With the expression of ASPN protein greatly reduced in keloid fibroblasts and nude mice allografts after treatment with si-ASPN, the collagen and fibroblasts were also uniform, thinner, parallel and regular. Conclusion: All the above experimental results suggest that keloid and ASPN are closely related and both fibroblast growth and metabolism of keloid are inhibited after silencing ASPN. Therefore, ASPN-siRNA delivered via nanoparticles can serve as a novel intervention therapy for the treatment of keloids.